Model Pembelajaran Kooperative Tipe Teams Games Tournament (TGT): Pengaruhnya Terhadap Pemahaman Konsep - Ulfia, Tara; Irwandani, Irwandani (Indonesian Journal of Science and Mathematics Education, 2019)
Abstract: This study aims to determine the effect of the TGT model on the understanding of students' concepts. The research method used was quasi-experimental with a non equivalent control group design. The population in this study amounted to 76 students, with samples VIII C as the experimental class and VIII A as the control class. The sampling technique uses cluster random side. To measure the understanding of concepts students are tested with multiple choice questions amounting to 20. Test hypotheses are used to determine whether or not there is an influence of the TGT model on students' conceptual understanding. The results of the analysis state that there is an influence on understanding the concepts of students. This is evidenced from the acquisition of tcount more than t table, which is 4.933 more than 2.011, which means that, there is the influence of the TGT learning model on students' conceptual understanding.Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh model TGT terhadap pemahaman konsep peserta didik. Metode penelitian yang digunakan adalah kuasi eksperimen dengan desain non equivalent control group. Populasi dalam penelitian ini berjumlah 76 peserta didik, dengan sampel VIII C sebagai kelas eksperimen dan VIII A sebagai kelas kontrol. Teknik pengambilan sampel menggunakan cluster random samping. Untuk mengukur pemahaman konsep peserta didik dilakukan tes dengan soal pilihan ganda berjumlah 20. Uji hipotesis digunakan untuk mengetahui ada atau tidaknya pengaruh model TGT terhadap pemahaman konsep peserta didik. Hasil analisismenyatakan bahwa terdapat pengaruh terhadap pemahaman konsep peserta didik. Hal ini dibuktikan dari perolehan nilai thitung lebih dari ttabel yaitu 4,933 lebih dari 2,011 yang berarti bahwa, terdapat pengaruh model pembelajaran TGT terhadap pemahaman konsep peserta didik.